Optimized Interfaces in Anti-Perovskite Electrolyte-Based Solid-State Lithium Metal Batteries for Enhanced Performance - Yu, Pengcheng; Ye, Yu; Zhu, Jinlong; Xia, Wei; Zhao, Yusheng (Frontiers in Chemistry, 2021)
Solid-state lithium metal batteries have attracted broad interest as a promising energy storage technology because of the high energy density and enhanced safety that are highly desired in the markets of consumer electronics and electric vehicles. However, there are still many challenges before the practical application of the new battery. One of the major challenges is the poor interface between lithium metal electrodes and solid electrolytes, which eventually lead to the exceptionally high internal resistance of the cells and limited output. The interface issue arises largely due to the poor contact between solid and solid, and the mechanical/electrochemical instability of the interface. In this work, an in-situ “welding” strategy is developed to address the interfacial issue in solid-state batteries. μL-level of liquid electrolyte is transformed into an organic-inorganic composite buffer layer, offering a flexible and stable interface and promoting enhanced electrochemical performance. Symmetric lithium-metal batteries with the new interface demonstrate good cycling performance for 400 hours and withstand the current density of 0.4 mA cm-2. Full batteries developed with lithium-metal anode and LiFePO4 cathode also demonstrate significantly improved cycling endurance and capacity retention.